Earthquake response of arch dams to spatially varying ground motion. - Chopra, Anil K. (Earthquake engineering & structural dynamics.)
The response of two arch dams to spatially varying ground motions recorded during earthquakes is computed by a recently developed linear analysis procedure, which includes dam?water?foundation rock interaction effects and recognizes the semi-unbounded extent of the rock and impounded water domains. By comparing the computed and recorded responses, several issues that arise in analysis of arch dams are investigated. It is also demonstrated that spatial variations in ground motion, typically ignored in engineering practice, can have profound influence on the earthquake-induced stresses in the dam. This influence obviously depends on the degree to which ground motion varies spatially along the dam?rock interface. Thus, for the same dam, this influence could differ from one earthquake to the next, depending on the epicenter location and the focal depth of the earthquake relative to the dam site.